-n + .4n + 1.8 = -3 ...i know the answer is 8, but cant seem to come to that conclusion myself.
also, 5(x-2) - (-x + 3) = 7 ...i know the answer is 10/3 but cant seem to get there on my own either.
Thanks in advance
I presume you know that "-n" is the same as "(-1)n" and that, by the "distributive law", (-1)n+ .4n= (-1+ .4)n= -.6n. So the equationis the same as -.6n+ 1.8= -3. Now subtract 1.8 from both sides: -.6n= -4.8 and, finally, divide both sides by -.6.-n + .4n + 1.8 = -3 ...i know the answer is 8, but cant seem to come to that conclusion myself.
also, 5(x-2) - (-x + 3) = 7
Again you need the "distributive law". 5(x- 2)= 5x- 10 and -(-x+ 3)= -(-x)- 3= x- 3. Using those, the equation becomes 5x- 10+ x- 3= 7. Of course, 5x+ x= 6x and -10- 3= -13 so that is 6x- 13= 7. Adding 13 to both sides gives 6x= 20 and then divide both sides by 6....i know the answer is 10/3 but cant seem to get there on my own either.
Thanks in advance